Critical studies on the Mahābhāsya - Limaye, V. P. (Vishnu Prabhakar), 1900- (Vishveshvaranand Vedic Research Institute publication ;, 1974)
Study of Patanjali's exegesis of Panini's Aṣṭādhyāyī, Sanskrit grammatical treatise.